Improvement of pavement foundation response with multi-layers of geocell reinforcement: cyclic plate load test - Khalaj, Omid; Tafreshi, Seyed Naser Moghaddas; Mask, Bohuslav; Dawson, Andrew (Techno Press, 2015)
Comprehensive results from cyclic plate loading at a diameter of 300 mm supported by layers of geocell are presented. The plate load tests were performed in a test pit measuring in plane and 700 mm in depth. To simulate half and full traffic loadings, fifteen loading and unloading cycles were applied to the loading plate with amplitudes of 400 and 800 kPa. The optimum embedded depth of the first layer of geocell beneath the loading plate and the optimum vertical spacing of geocell layers, based on plate settlement, are both approximately 0.2 times loading plate diameter. The results show that installation of the geocell layers in the foundation bed, increase the resilient behavior in addition to reduction of accumulated plastic and total settlement of pavement system. Efficiency of geocell reinforcement was decreased by increasing the number of the geocell layers for all applied stress levels and number of cycles of applied loading. The results of the testing reveal the ability of the multiple layers of geocell reinforcement to 'shakedown' to a fully resilient behavior after a period of plastic settlement except when there is little or no reinforcement and the applied cyclic pressure are large. When shakedown response is observed, then both the accumulated plastic settlement prior to a steady-state response being obtained and the resilient settlements thereafter are reduced. The use of four layers of geocell respectively decreases the total and residual plastic settlements about 53% and 63% and increases the resilient settlement 145% compared with the unreinforced case. The inclusion of the geocell layers also reduces the vertical stress transferred down through the pavement by distributing the load over a wider area. For example, at the end of the load cycle of the applied pressure of 800 kPa, the transferred pressure at the depth of 510 mm is reduced about 21.4%, 43.9%, 56.1% for the reinforced bases with one, two, and three layers of geocell, respectively, compared to the stress in the unreinforced bed.